PENGEMBANGAN SISTEM SMART SHIP SAFETY MELALUI KOLABORASI IoT DAN CONDITION-BASED MAINTENANCE MESIN KAPAL: Development of a Smart Ship Safety System Through IoT Collaboration and Condition-Based Maintenance of Ship Engines - Saphira, Namira Najwa; Namira; Reval; Khafid (PT Yupin Felicitas Utama, 2025)
Ship operational safety has become a top priority in today's maritime world, with the need for reliable and efficient performance. This research has successfully produced Smart Ship Safety through a combination of Internet of Things service solutions and a Condition-Based Maintenance approach, used to detect potential hazards and perform maintenance. In this project, the solution is based on tilt sensors, GPS modules, and windlass hydraulic motor monitoring, which are connected to the engine via a web-based platform and help control the stability of the ship and engine. Model development was carried out using mathematical simulations. Furthermore, because it is based on CBM, another crucial aspect is identifying engine component degradation, allowing for prompt replacement before major failures occur. The final results reported by the project have improved the accuracy of CBM in diagnosing engine conditions by 30%, reduced emergency maintenance costs, and reduced the risk of engine failure or ship braking. Keywords: Smart Ship Safety, IoT, Condition-Based Maintenance, Hydraulic Motor, Maritime Safety